THE RELATIONSHIP OF THE PHYSICAL READINESS DETERMINANT FOR THE COMPOSITE SKILL PERFORMANCE OF FOOTBALL PLAYERS - Abdullah Mohammed Rahim; Prof. Dr. Abdulmoneim A. Jassim Aljanabi (Proximus Journal Publishing, 2025)
The research community consisted of players of second-division football clubs in Kirkuk Governorate participating in the second division league competitions for the football season (2023-2024), which numbered (17) clubs, and the number of players distributed to these clubs was (322) players, and the researchers identified the most important physical measurements appropriate for the research sample as well as choosing the composite skill performance test, and then the main experiment was applied and they obtained the data for the special physical determinant and complex skill performance test and processed by statistical (SPSS).
Keywords: determinant; physical; complex